Risk communication and earthquake psychology: a research on earthquake news - Sevgi Kavut (Vivat Academia)
Introduction: Risk communication is an inseparable part of any immediate reply. Earthquakes are complicated emergencies that exacerbate issues with risk communication and highlight these issues for scientists to communicate about. Turkey is vulnerable to various natural disasters, including earthquakes, floods, landslides, and thunderstorms, due to its geographic location and climate. In the process of dealing with natural disasters, risk awareness and risk communication have become crucial. Methodology: The goal of this study is to examine how the earthquake and risk communication affects society with the content analysis method in the context of the Kahramanmaraş earthquakes, which occurred on February 6. The news on four internet news websites was analyzed using the content analysis method in the context of the earthquakes centered on Kahramanmaraş on February 6. Frequency analyses were made in the context of the determined research questions and topics. Results: As a result of the study, it was found that the most frequently mentioned news items are earthquake news, news with a positive news tone, and agenda news. The informative category ranks first in the category of news publication aims. Discussion: When news is analyzed based on news tone, it is found that stories with a positive tone rank higher than those with a negative or neutral tone. Conclusions: This research contributes to furthering the fields of risk communication, disaster communication, risk awareness, and earthquake and disaster psychology.